2020
DOI: 10.1038/s41586-020-2785-8
|View full text |Cite|
|
Sign up to set email alerts
|

The genomic landscapes of individual melanocytes from human skin

Abstract: Every cell in the human body has a unique set of somatic mutations, yet it remains difficult to comprehensively genotype an individual cell. Here, we developed solutions to overcome this obstacle in the context of normal human skin, thus offering the first glimpse into the genomic landscapes of individual melanocytes from human skin. We comprehensively genotyped 133 melanocytes from 19 sites across 6 donors. As expected, sun-shielded melanocytes had fewer mutations than sun-exposed melanocytes. However, within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 54 publications
4
72
2
1
Order By: Relevance
“…1a for an example). To account for each of these potential issues, we used the Footprints software 23 to count the exact number of basepairs in each sample with sufficient sequencing coverage to make a mutation call. For the average sample, we could detect mutations at 91.2% of target bases, though this ranged from 52.3% to nearly 100% (Supplementary Fig.…”
Section: Assembling a Cohort Of Cutaneous Squamous Cell Carcinomasmentioning
confidence: 99%
“…1a for an example). To account for each of these potential issues, we used the Footprints software 23 to count the exact number of basepairs in each sample with sufficient sequencing coverage to make a mutation call. For the average sample, we could detect mutations at 91.2% of target bases, though this ranged from 52.3% to nearly 100% (Supplementary Fig.…”
Section: Assembling a Cohort Of Cutaneous Squamous Cell Carcinomasmentioning
confidence: 99%
“…Recent studies have revealed the somatic mutation landscape of different normal human tissues, including the skin 3,4 , esophagus 5,6 , colon and rectum 7 , liver 8 , endometrial epithelium 9 , bronchia 10 , brain 11,12 , embryo 13 , urothelium 14,15 , and blood cells 16,17 , mostly through deep DNA sequencing of biopsied tissue samples. Other studies have implemented bioinformatic algorithms to detect somatic mutations from RNA sequencing data of normal human tissues 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Dans un travail récent particulièrement bien conduit, les auteurs font progresser ce problème de manière significative [2]. Ayant choisi de s'intéresser aux mélanocytes, ils révèlent un riche paysage mutationnel chez des cellules de personnes âgées (63 à 85 ans) d'origine européenne, vivantes ou récemment décédées et atteintes ou non de mélanomes.…”
Section: French Versionunclassified
“…In a particularly well-conducted recent work, the authors have made significant progress in addressing this problem [2]. Having chosen to focus on melanocytes, they reveal a rich mutational landscape in cells derived from elderly (63 to 85 years old) people of European origin, living or recently deceased, with or without melanoma.…”
mentioning
confidence: 99%